Impact of land use change on ecosystem services: A review - Hasan, Shaikh Shamim; Zhen, Lin; Miah, Md. Giashuddin; Ahamed, Tofayel; Samie, Abdus (Environmental development, 2020)
Changes in land use and ecosystem services influence each other and such changes have consequences for human wellbeing. In this paper, we review the research literature on how different types of ecosystem services are affected by LUC, and the consequences for human well-being. We begin with a review of the different types of ecosystem services. We examine the influence of LUC on provisioning ecosystem services due to mismatches between agricultural production and hydrological systems. We continue with a review of the impacts of LUC on supporting ecosystem services through the conversion of an ecosystem to cultivated land, and the resulting changes in soil properties and the hydrological balance. Next, We also discuss the regulating ecosystem services which are affected by LUC and alters water purification processes, as well as the effects on cultural ecosystem services. We conclude with a review of the valuation and quantification of the effects of LUC on the management of ecosystem services, and propose future research directions. Most of the research reveals a negative impact of LUC on ecosystem services, despite research gaps related to methods for valuing ecosystem services more accurately and for collecting social responses to the impacts of LUC on different ecosystem services. •Different land use and cover change (LUCC) factors like population and economic expansion, built-up area expansion, etc. have forced human being to convert agricultural land to non agricultural purposes.•Most of the countries of the world faced the same experience of land cover change which hampers the food security status.•The Remote sensing data were used to accurately analyze and understood this change.•All types of ecosystem services, ie., supporting, provisioning, regulating or cultural are influenced by different factors.•Social responses to the effects of changes in ecosystem services remain poorly researched.